ADAPTASI ELEMEN RUANG PEDESAAN TERHADAP KEGIATAN PARIWISATA DI KAWASAN BOROBUDUR - Prakoso, Aditha Agung; Irawati, Novi (Aksen : Journal of Design and Creative Industry, 2022)
The Borobudur area is a cultural heritage area that is not only an ancestral cultural heritage but also a tourist attraction. The development of heritage tourism in the Borobudur area has developed not only around the temple. However, it has developed into the residential area of the surrounding villagers as a rural tourism activity. This tourism activity impacts changes in elements of rural space, such as houses, public facilities, and roads, thus affecting the authenticity value as a rural tourist attraction, which is the basis for developing a tourist village. The setting and resources, the basic concept of a tourist village, are the spatial system of changing rural space elements. This spatial change of elements is caused by the spatial adaptation made by the user due to changes in ideas and behavior, which are influenced by additional functions in the space element. This study aims to explain the process of adapting spatial elements in tourist villages in the Borobudur area, using a rationalistic qualitative research method with multiple case studies with case units of 3 tourist villages in the Borobudur area, including Borobudur, Candirejo, and Wanurejo villages. The research findings are the process and form of adaptation of rural spatial elements. This research is expected to be used for village development to maintain its authenticity value as a tourist attraction. Keywords: adaptation, spatial elements, tourism village, Borobudur